Estudio socioeconómico-educativo de los estudiantes de la Unidad Educativa “Italia” del cantón Santiago. - Tonato Mocha, Arleth Aracelly (2023)
Determining the socioeconomic-educational situation of the 2nd and 3rd year BGU students of the "Italia" Educational Unit of Canton Santiago, province of Morona Santiago, is a factor that allows knowing the reality that students go through, which leads to observing the quality of life of their families, their social and economic status, as well as the inequality that encompasses the educational sector. Methodologically, the study used a mixed approach, non-experimental, basic, field, and descriptive design; the population that formed part of this study were the institution's students, belonging to the second and third year of BGU. In the data collected, non-probabilistic and purposeful sampling was used. The technique was the survey, an element that facilitated the identification of the environment in which students develop and the social influence that represents both economic, educational, and family. All these elements affect the quality of life because they have had to face new experiences sometimes due to a lack of stable work for their families, thus triggering family conflicts and economic, among others; These elements are reflected in the results obtained since there is tangible evidence that in certain cases the lack of resources forces them to look for work, neglecting their studies and being forced to be one more economic support of the household, which causes the students to refuse to continue with their higher education because they consider it impossible due to the lack of support from their family and the financial situation of their homes.